Benign Prostatic Hyperplasia Conservative and Operative Management - Jakse, Gerhard; Bouffioux, Christian; Leval, Jean de; Janknegt, Rudi A. (Springer Berlin Heidelberg, 1992)
An intense discussion has recently begun regarding current standards in the diagnosis and treatment of benign prosta tic hyperplasia (BPH). A number of factors have led to this discussion. In an increasing proportion of aging men, for example, BPH causes so-called obstructive symptoms that must be relieved by medical or operative means. This entails an immense social and economic impact in terms of health costs. In addition, recent data indicate the most frequently performed operation for BPH - transurethral resection of the prostate - is associated with a higher risk of death due to cardiac disease than open prostatectomy. Furthermore, studies using the recently developed technique of uro dynamics to assess bladder outflow obstruction reveal that about 20% -30% of patients treated with transurethral resection or open prostatectomy are actually not obstructed. This means that these patients do not receive the most effective therapy. Finally, various new treatment been developed, including medical treat modalities have ment directed at endocrine pathways in the prostatic cells, balloon dilatation, spirals, temporary or permanent stents, C). nd the application of heat in hyperthermia or thermo therapy. The contributions to this volume were selected from a symposium on the diagnosis and treatment of BPH. They are intended to provide a comprehensive review of the state of the art in treating BPH. Aachen, Liege, Maastricht, September 1992 The Editors Contents Development of Benign Prostatic Hyperplasia 1 J. E. Altwein and H. Baur Bladder Outflow Obstruction: Definition, Clinical Application, and Grading in Benign Prostatic Hyperplasia. . . . . .
Keywords: Urology; Surgery; Prostatahypertrophie; Therapie; Konferenzschrift